Production of sexed bovine embryos in vitro can be improved by selection of sperm treatment and co-culture system - Travnickova, Ivona; Hulinska, Pavlina; Kubickova, Svatava; Hanzalova, Katerina; Kempisty, Bartozs; Nemcova, Lucie; Machatkova, Marie (Reproduction in domestic animals, 2021)
The study investigated the effects of sperm sorting, capacitation treatment and co-cultivation on sexed bovine in vitro embryo production. The effect of treatment and co-culture on production of embryos of the preferred sex from unsorted sperm was also studied. Sperm from five breeding bulls was used for fertilization of mature oocytes as follows: Experiment 1, sorted and unsorted sperm (bulls A-E) treated only with heparin in standard co-cultures; Experiment 2, sorted sperm (bulls A-E) treated with heparin-PHE (penicillamine, hypotaurine, and epinephrine) or heparin-caffeine in drop co-cultures; and Experiment 3, unsorted sperm (bull E) treated with either heparin-PHE or heparin-caffeine in both standard and drop co-cultures. In all bulls, treatment with heparin resulted in significantly (p < .05) reduced cleavage and blastocyst rates from sorted sperm, as compared with those from unsorted sperm. In bulls A, B, D and E, treatment of sorted sperm with heparin-PHE in drops significantly increased the blastocyst rate (p < .05). In unsorted sperm of bull E, heparin-PHE treatment in drops resulted in the XX/XY sex ratio inverse to that obtained by heparin-caffeine treatment in standard co-cultures (32.3%/67.7% and 66.7%/33.3%, respectively). In conclusion, the treatment of sorted sperm with heparin-PHE in modified drop co-cultures can be recommended for production of in vitro sexed embryos. The use of unsorted sperm for production of embryos of the preferred sex by selected capacitation treatment and co-culture can be the method of choice in bulls with low IVF yields from sorted sperm.
Keywords: spermie; předvýběr pohlaví; Epinephrine; capacitation treatment; sorting; kokultivační techniky; fertilizace in vitro; Embryo Culture Techniques; IVF; Female; kultivace embrya; sexed embryos; zvířata; heparin; Taurine; Fertilization in Vitro; oocyty; Penicillamine; sperm; Coculture Techniques; Heparin; Cattle; ženské pohlaví; Male; adrenalin; breeding bulls; skot; penicilamin; Spermatozoa; Sex Preselection; Animals; mužské pohlaví; Oocytes; taurin